KEPERANTARAAN (WASATHAH) DAN PENERAPAN AKAD YANG TERJADI DI DALAMNYA - Muhamad Izazi Nurjaman; Arzam Arzam; Doli Witro (Program Studi Perbankan Syariah, Fakultas Ekonomi dan Bisnis Islam, IAIN Fattahul Muluk Papua, 2022)
This article is motivated by the rapid development of the intermediary business which is very much needed in the marketing mechanism. Intermediary in sharia economic law includes new contracts. However, in practice the use of intermediary contracts is schemed in other forms of contracts, such as in the DSN-MUI fatwa on intermediary. Therefore, this article will reveal the intermediary and application of the contract that occurs in it. This article is a study of sharia economic law by taking into account the fiqh of muamalah maliyyah as an analytical lens. Sources of data obtained in the form of primary data sources in the form of DSN-MUI fatwa and secondary data in the form of various scientific literature in the form of books and scientific journals. By using a normative juridical approach that is presented through a descriptive literature method, this study finds the fact that the application of intermediary contracts (wasathah) in sharia economic law can be discussed in wakalah bi al-ujrah, ju’alah and bai’ al-samsarah contracts. So that the use of one of these contracts will affect the mechanism for implementing the contract and the benefits obtained by the wasit party, namely in the form of ujrah from the wakalah bi al-ujrah contract, ju’l from the ju’alah contract and the margin from the excess of the bai’ al-samsarah contract. This shows that the wasathah contract is a contract scheme that adapts to the practices and needs of the community for intermediary services. The implementation of these contracts provides legal certainty in their implementation in accordance with sharia economic principles.